2012
DOI: 10.1002/hpm.2146
|View full text |Cite
|
Sign up to set email alerts
|

Removal of user fees for caesareans and under‐fives in northern Sudan: a review of policy implementation and effectiveness

Abstract: In 2008, the Government of Sudan launched a policy of free curative care for under-fives and caesareans. This paper presents the findings of a review of this policy, on the basis of research conducted in five focal states of northern Sudan in 2010. Policy implementation was assessed using four research tools: key informant interviews, exit interviews, a facility survey, and analysis of facility finances and the cost of the package of care. The findings point to important weaknesses in implementation, such as u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…A policy of providing free care for caesareans and under-fives was launched in 2008 in northern Sudan. A review done two years later found that normal deliveries increased by 14% [ 18 ]. Ghana introduced a free maternal care initiative in 2008.…”
Section: Discussionmentioning
confidence: 99%
“…A policy of providing free care for caesareans and under-fives was launched in 2008 in northern Sudan. A review done two years later found that normal deliveries increased by 14% [ 18 ]. Ghana introduced a free maternal care initiative in 2008.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted interviews with women who gave birth, their husbands or their relatives who accompanied them to the hospital when they were about to leave the health facility. The interviews were conducted using a structured questionnaire that was used in Sudan for a similar survey . This questionnaire was adapted to the Moroccan context and then tested at a maternity hospital before being implemented in the different study sites.…”
Section: Methodsmentioning
confidence: 99%
“…Data from Demographic and Health Surveys conducted in ten SSA countries found that the policy change was consistent with an increase of 3.1 facility deliveries per 100 live births, which corresponds to a 5 % increase in facility deliveries, with no corresponding increase in the rate of CS [ 45 ]. In Sudan, the free care policy applied only to CS and not to vaginal delivery, but utilization of services still increased 14 %; authors noted, however, that this policy was implemented without the resources to support it, which still led to a significant portion of the cost being born by the woman and her family [ 46 ].…”
Section: Cost Of Cesarean Section In Ssamentioning
confidence: 99%